Viruses Challenge Selectivity Barrier of Nuclear Pores - Labokha, Aksana A. (MDPI, 2013)
Exchange between the nucleus and the cytoplasm occurs through nuclear pore complexes (NPCs) embedded in the double membrane of the nuclear envelope. NPC permeability barrier restricts the entry of inert molecules larger than 5 nm in diameter but allows facilitated entry of selected cargos, whose size can reach up to 39 nm. The translocation of large molecules is facilitated by nuclear transport receptors (NTRs) that have affinity to proteins of NPC permeability barrier. Viruses that enter the nucleus replicate evolved strategies to overcome this barrier. In this review, we will discuss the functional principles of NPC barrier and nuclear transport machinery, as well as the various strategies viruses use to cross the selective barrier of NPCs.